The Impact of Celebrity Endorsers, Price, and Product Quality on Purchase Decision of Yamaha Maxi Motorcycles in Pekanbaru City: An Exploratory Study - Wahyudi, Beny; Noviasari, Henni; Musfar, Tengku Firli; Siregar, Prima Andreas (Westscience Press, 2023)
This research aims to examine the influence of celebrity endorsers, price and product quality on purchasing decisions for Yamaha Maxi motorbikes in the city of Pekanbaru. The type of data used in the research is quantitative. The population in this study includes all Yamaha Maxi motorbike consumers in Pekanbaru City. The sampling technique used a non-probability sampling method which was purposive sampling, totaling 128 respondents. Data was collected with the help of a questionnaire and then the data was processed using multiple linear regression analysis with the help of SPSS version 22 software. The research results showed that: 1) Celebrity Endorser had a significant positive effect on Purchase Decisions for Yamaha Maxi motorbike products in the city of Pekanbaru. 2) Price has a significant positive effect on purchasing decisions for Yamaha Maxi motorbike products in the city of Pekanbaru. 3) Product quality has a significant positive effect on purchasing decisions for Yamaha Maxi motorbike products in the city of Pekanbaru. 4) Celebrity Endorser, Price and Product Quality simultaneously have a significant positive effect on Purchase Decisions for Yamaha Maxi motorbike products in the city of Pekanbaru.